Hubungan Kekurangan Energi Kronis (KEK) dengan Kejadian Anemia pada Ibu Hamil - Richa Agusmarinda; Yustina Ananti; Indah Purnamasari (Jurnal Kesehatan Amanah, 2025)
Pregnancy is a critical period for determining future human resource quality as fetal development starts in the womb Pregnant women are vulnerable to nutritional issues such as anemia, which occurs when hemoglobin levels decrease and fail to meet the body’s oxygen needs, as well as Chronic Energy Deficiency (CED), which can worsen this condition. CED in pregnant women increases the risk of anemia and negatively impacts the health of the mother and fetal growth. The purpose of this study is to investigate the relationship between chronic energy deficiency and the incidence of anemia in pregnant women in the working area of Kampung Kawat Health Center in 2024. This quantitative study utilizes a cross-sectional approach. Purposive sampling is used as the sampling technique, with a total of 67 pregnant women as respondents. Data were collected directly through medical records, anthropometric measurements, and hemoglobin level analysis to identify CED and anemia. Chi-square tests were applied to test the hypothesis. The analysis revealed that 20 respondents (29.8%) experienced both anemia and CED, while 31 respondents (46.3%) did not experience either condition. The Chi-square test produced a p-value of 0.000 (p < 0.05) and an Odds Ratio (OR) of 0.000 (<0.05), proving a significant relationship between CED and anemia. The Confidence Interval (CI) of 9.841 (3.159–30.663) further supports the significant relationship between CED and anemia in pregnant women. Chronic Energy Deficiency is significantly associated with an increased risk of anemia in pregnant women in the working area of Kampung Kawat Health Center in 2024.